PENUMBUHAN BUDAYA LITERASI MELALUI SOSIALISASI PENTINGNYA LITERASI SERTA PENGADAAN KELAS CALISTUNG DI SD N 2 DARMASABA - Ida Ayu Made Wedasuwar,; Ni Luh Putu Wulandari,; Putu Sista Dewi, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This service activity was carried out to foster and develop a culture of literacy among students at SD N 2 Darmasaba. This activity was initiated after observing at SD N 2 Darmasaba, where there were students who were still not proficient in reading, writing and calculating activities and whose literacy interest needed to be improved. In this service activity, the service team carried out a series of activities including providing outreach about the importance of literacy which was then continued with additional calistung teaching assistance. The results of this activity showed that students gave a positive response, namely 94.33% of students felt that this activity had a positive impact on them. The school hopes that activities like this can be carried out continuously to increase students' understanding.